INTEREST IN PROGRAMMING THROUGH THE USE OF THE PYGAME ZERO MODULE IN THE 7TH GRADE OF THE NEW UKRAINIAN SCHOOL - Kysil , Tetyana Oleksandrivna (Distance Education in Ukraine: Innovative, Normative-Legal, Pedagogical Aspects, 2025)
The article examines the problem of interest in programming among 7th grade students of the New Ukrainian School (NUS). The relevance of using the Pygame Zero module as a tool that combines ease of use with the ability to create visually attractive projects is substantiated. The pedagogical experience of implementing Pygame Zero in computer science lessons is presented, examples of educational tasks are given.